The effect of climate on the spread of wheat rust diseases in Baghdad governorate - Khayoun, Zainab; Abdel Hussein, Oras (Al-Adab Journal, 2024)
Wheat rust diseases are considered one of the serious fungal diseases, and it is one of the most harmful diseases on the wheat crop. (25-3°C( and moderate nights (15-20 °C). This disease is suitable for continuous humidity in the air, rainfall in spring, and warm weather, as well as leaf rust (orange) with high humidity, with a large difference between day and night temperatures. The temperature ranges from (20-25) during the day, from (15-20) at night, and the severity of the infection varies from one season to another according to the appropriate environmental conditions for the spread of the disease and the spread of uremic germs. As for yellow rust, it is affected by three climatic elements: wind, temperature and humidity. Bacteria on the leaves with temperatures suitable for the disease to occur from (6-12) C at night and (12-18 C) during the day, and high humidity with a large difference between the night and day temperature plays a major role in the occurrence of yellow rust.